Regional responses to U.S.-China competition in the Indo-Pacific study overview and conclusions - Lin, Bonny; Chase, Michael S.; Blank, Jonah; Cooper, Cortez A. III; Grossman, Derek; Harold, Scott 1975-; Moroney, Jennifer D. P. 1973-; Morris, Lyle J.; Ma, Logan; Orner, Paul; Shih, Alice; Kim, Soo (RAND Corporation, 2020)
In long-term strategic competition with China, how effectively the United States works with allies and partners will be critical to determining U.S. success. To enable closer cooperation, the United States will need to understand how allies and partners view the United States and China and how they are responding to U.S.-China competition. In this report, which is the main report of a series on U.S.-China competition in the Indo-Pacific, the authors define what U.S.-China competition for influence involves and comparatively assess U.S.-China competition for influence in six countries in Southeast Asia-Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam-as well as the roles of three U.S. allies and partners that are active in Southeast Asia-Australia, India, and Japan. The authors first explore why the United States is competing with China in the Indo-Pacific and what the two are competing for. They then develop a framework that uses 14 variables to assess relative U.S.-Chinese influence across countries in the Indo-Pacific. Drawing from interviews in all nine countries and data gathered, the authors apply this framework to assess how regional countries view U.S.-China competition in their respective countries and how China views competition in each of the regional countries. Finally, the authors discuss how the United States could work more effectively with allies and partners in Southeast Asia and beyond
"RAND Project AIR FORCE."
"Prepared for the United States Air Force."
Keywords: Einflussnahme; China; Südostasien; USA; United States / Foreign relations / China / 21st century; China / Foreign relations / United States / 21st century; Great powers / Foreign relations; Security, International / Indo-Pacific Region; Security, International / Southeast Asia; Diplomatic relations; Security, International; Indo-Pacific Region; Southeast Asia; United States; 2000-2099